The advertisement call of Chiasmocleis (Syncope) carvalhoi (Nelson, 1975) (Anura: Microhylidae), with taxonomic remarks based on new morphological observations of specimens from Peruvian Amazonia - Rojas-Padilla, Omar; Gagliardi-Urrutia, Giussepe; Simões, Pedro Ivo; Castroviejo-Fisher, Santiago (Zootaxa, 2020)
We quantitatively describe for the first time the advertisement call of Chiasmocleis (Syncope) carvalhoi using recordings  of five specimens from northern Peruvian Amazonia. The advertisement call is characterized by a single, short, tonal, and high-pitched note. Call duration ranges between 0.03–0.06 s and its dominant frequency between 7.12–7.92 kHz. The lack of pulses within notes distinguishes C. (Syncope) carvalhoi from all congeneric species except C. (Syncope) antenori, C. (Syncope) parkeri and C. (Chiasmocleis) mantiqueira, which can be distinguished by the shorter duration of their notes and silent intervals (in C. (Syncope) antenori and C. (Syncope) parkeri) and by the lower dominant frequency (in C. (Syncope) parkeri and C. (Chiasmocleis) mantiqueira). In addition, based on our collected specimens, we report on and discuss about the variation of some external morphological characters and natural history of C. (Syncope) carvalhoi, including the absence of vocal slits and sacs. Our study reveals a potential association between the absence of vocal slits and sacs, and tonal calls in Chiasmocleis, as well as conflicting morphological diagnostics characters in the literature.